(untitled) - Stahl, S. M. (Cambridge, U.K.,New York, 2000)
Essential Psychopharmacology has established itself as the preeminent source of information in its field, and this book draws on the second edition to provide a resource for all clinicians involved in the treatment of depression and bipolar disorder. Stressing the basic neuroscience of the mood disorders, the fully updated text and color illustrations enable readers to understand how the various antidepressants and mood stabilizers work in their patients. It contains new information on the pharmacokinetics of antidepressants, including the role of the cytochrome P450 enzyme system and neuropeptides including substance P. The mechanisms of action of newer antidepressants, including the latest SSRIs, are prominently and authoritatively reviewed. Psychiatrists, primary care physicians and mental health professionals can depend on this book for an up-to-date account of the psychopharmacology of mood disorders, and for essential information in planning treatment approaches
Keywords: Depression, Mental,Manic-depressive illness,Psychopharmacology,Chứng rối loạn thần kinh,Chứng suy nhược thần kinh,Hóa học trị liệu; Chemotherapy,Chemotherapy